Ekstrak Pollen Kurma (Phoenix dactylifera L) Sebagai Terapi Infertilitas Pada Pria - Devi Rahmadiani (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction Infertility is one of the problems faced by couples who want to have children. Infertility in a year occurs as much as 15% in couples who expect pregnancy. Aim; analyzed that the antioxidant content in DPP can counteract free radicals and prevent oxidative stress. Method; The analysis is carried out with a systematic literature review method by examining, identifying, assessing, and presenting it. Result; found various studies showing that DPP extract has an effect to prevent and treat infertility. Conclusion; that there is a decrease in sperm quality due to increased oxidative stress due to an imbalance of antioxidants and free radicals